(untitled) (Modern American Journal of Social Sciences and Humanities, 2025)
The article discusses the transformation of ecological culture and religious values, their role in positively changing people’s attitudes towards the environment and Mother Nature, and the importance of tackling global ecological problems and their negative consequences such as water scarcity and global climate change.